The evolution of the concept of «foreign debt» as an indicator of financial security (Economics and region, 2018)
This article studied the evolution of theoretical concepts of foreign and domestic scientists and economists about the concept of external debt. In the course of the study revealed reasoned opinion mercantilists, physiocrats, the representatives of the English classical school, Marxist, Keynesian economics, and modern scientists to the determination of the nature and value of the external public debt of the country; it demonstrated the influence of external public debt to financial security and develop its own approach to the definition of the external public debt. At the present stage of development of economy of external public debt represents the total liabilities of the state, expressed by a sum of money to be repaid to foreign creditors of a certain date, that is, the total debt of the country on foreign loans and unpaid interest thereon. The growth of external public debt is dangerous, in fact, causes an outflow of foreign exchange reserves abroad, creating an additional burden on the balance of payments, and finally, in terms of inefficient public debt management can lead to the insolvency of the borrower country. Scientific novelty lies in the improvement of the existing definitions of external public debt by combining different approaches of economists. Prospects for further research is the study of the sources and uses mobilization of external public debt in order to determine the strategic priorities of the debt policy of Ukraine at the present stage of economic reforms.
Keywords: external debt; deficit financing; the economic burden; debt security indicator